Cinnamaldehyde as a Promising Dietary Phytochemical Against Metabolic Syndrome: A Systematic Review - Khaafi, Mohaddeseh; Tayarani-Najaran, Zahra; Javadi, Behjat (Mini Reviews in Medicinal Chemistry, 2024)
Background: Metabolic syndrome (METS) is a set of unhealthy medical conditions considered essential health problems today. Cinnamaldehyde (CA) is the major phytochemical present in the essential oil of cinnamon and possesses antioxidant, anti-inflammatory, hypoglycemic, and antihyperlipidemic activities.Aim: We aim to systematically review the effects of CA in preventing and attenuating METS components. Moreover, the cellular and molecular mechanisms of actions of CA, its pharmacokinetics features, and potential structure-activity relationship (SAR) were also surveyed.Methods: PubMed, Science Direct, Scopus, and Google Scholar were searched to retrieve the relevant papers.Results: CA possesses various anti-METS activities, including anti-inflammatory, antioxidant, antidiabetic, antidyslipidemia, antiobesity, and antihypertensive properties. Various molecular mechanisms such as stimulating pancreatic insulin release, exerting an insulinotropic effect, lowering lipid peroxidation as well as pancreatic islet oxidant and inflammatory toxicity, increasing the activities of pancreatic antioxidant enzymes, suppressing pro-inflammatory cytokines production, regulating the molecular signaling pathways of the PPAR-γ and AMPK in preadipocytes and preventing adipocyte differentiation and adipogenesis are involved in these activities.Conclusions: CA would effectively hinder METS; however, no robust clinical data supporting these effects in humans is currently available. Accordingly, conducting clinical trials to evaluate the efficacy, safe dosage, pharmacokinetics characteristics, and possible unwanted effects of CA in humans would be of great importance.
Keywords: diabetes